2018
DOI: 10.1097/md.0000000000012799
|View full text |Cite
|
Sign up to set email alerts
|

The association between IUGR and maternal inherited thrombophilias

Abstract: One of the risk factors for vascular obstetric complications, such as intrauterine growth restriction (IUGR), is inherited thrombophilias. Nevertheless, routine screening for thrombophilias is not endorsed in pregnant women due to their low prevalence and conflicting results of published studies regarding the usefulness of screening in these patients. The cause of IUGR remains unknown in almost 1 quarter of cases. There are no published studies evaluating the association of inherited thrombophilias and IUGR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…[20,21,22] Additionally, a case-controlled study that compared the incidence of FGR between healthy women and women with inherited thrombophilias without LMWH therapy revealed that LMWH untreated inherited thrombophilias represents risk factors for FGR. [4]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20,21,22] Additionally, a case-controlled study that compared the incidence of FGR between healthy women and women with inherited thrombophilias without LMWH therapy revealed that LMWH untreated inherited thrombophilias represents risk factors for FGR. [4]…”
Section: Discussionmentioning
confidence: 99%
“…For many decades inherited thrombophilias have been linked with venous thromboembolism (VTE) in pregnancy and the puerperium [1] and recurrent miscarriages. [2] However, since recently they have also been recognized as risk factors for numerous adverse pregnancy outcomes (APO), such as preeclampsia, [3] intrauterine growth restriction, [4] placental abruption, [5] and stillbirth. [6] Kupfermink et al showed that as much as 65% of women with preeclampsia, unexpected still birth, placental abruption, and fetal growth restriction (FGR) had some form of inherited thrombophilias.…”
Section: Introductionmentioning
confidence: 99%
“…The 10 th week and the 3 rd trimester of preg-nancy are considered as critical periods for manifestation of thrombophilia since the complication such as recurrent miscarriages, stillbirth in the third trimester, placental abruption with massive bleeding, retardation of fetal development may occur [10]. The presence of thrombophilia determines the risk of developing the first episode of VT; however, it is not recognized as a risk factor for its recurrence [18].…”
Section: Thrombophiliamentioning
confidence: 99%
“…Вчені при-пускають взаємозв'язок тромбозу з дефіцитом антитромбіну, гіпергомоцистеїнемією та фактором V Лейдена й варіаціями протромбіну G20210A і дефіцитом білка S [1]. За припущеннями науковців, близько 65,0 % усіх випадків негативних наслідків вагітності у вигляді затримки внутрішньоутробного розвитку плоду, прееклампсій і відшарувань плаценти провокуються ТФ [4,10], а 60,0 % таких наслідків спровоковані спадковою ТФ і викликаними нею ідеопатичними тромбоемболічними випадками [6], через що при наявності у вагітних ТФ їх відносять до групи підвищеного ризику [11].…”
Section: Introduction/вступunclassified